2020
DOI: 10.1002/pat.4879
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of chitosan/collagen/hydroxyapatite scaffolds with encapsulated Cissus quadrangularis extract

Abstract: Here, we demonstrated the fabrication of a composite scaffold (chitosan [CS], collagen [Col], and hydroxyapatite [HA]) with the incorporation of encapsulated Cissus quadrangularis (CQ) extract for tissue engineering applications. First, the crude extract of CQ loaded nanoparticles were synthesized via double emulsion technique using polycaprolactone (PCL) and polyvinyl alcohol (PVA) as oil and aqueous phases, respectively. Both PCL (20, 40, and 80 mg/mL) and PVA (0.5%, 1%, and 3% w/v) concentrations were varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Furthermore, the porous structure enables efficient oxygen and nutrient transport, maintaining a suitable microenvironment to promote wound healing [44]. However, the long processing time and uneven heat transfer during the freeze drying process might lead to heterogeneity of the fabricated scaffolds which is one of the drawbacks needed to be overcome for this technique [45].…”
Section: Freeze Dryingmentioning
confidence: 99%
“…Furthermore, the porous structure enables efficient oxygen and nutrient transport, maintaining a suitable microenvironment to promote wound healing [44]. However, the long processing time and uneven heat transfer during the freeze drying process might lead to heterogeneity of the fabricated scaffolds which is one of the drawbacks needed to be overcome for this technique [45].…”
Section: Freeze Dryingmentioning
confidence: 99%
“…In another study, grape seed, pomegranate peel, and jabuticaba peel extracts direct blend with scaffolds of nanohydroxyapatite and collagen showed potent anti-bacterial activity and offered a promising strategy to design novel biomaterials for bone tissue regeneration [ 60 ]. In addition, scaffolds containing herbal extracts, such as Cissus quadrangularis [ 61 ], kaempferol [ 62 ], aloe vera extract [ 63 ], and Elaeagnus Angustifolia extract [ 64 ], have shown a potential bone tissue regeneration ability. In addition, NGR1 significantly induces osteogenic differentiation of MC3T3-E1 cells in vitro [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HA/Col composites had been prepared through different fabricated techniques and were used in many bone defects as biomaterials for bone tissue engineering. The composite have been incorporated by different sizes (Nano-size and micro-size) with many other materials such as calcium phosphate (CaP) [20], poly(L-lactide) (PLLA) [21], Poly(vinyl alcohol) (PVA) [22], chitosan [23], and metals such as iron (Fe) [24], to develop the properties of the composites, which will possess high compatibility and bio-degradable properties for bone repair.…”
Section: Preparation Methods Of Ha/col Compositesmentioning
confidence: 99%
“…The previous studies have been reported to prepared the composites of HA/Col with natural polymers such as gelatine [25], cellulose [26], chitosan [27], chitin [28] and starch [29] as it shown in the table 2. Kaviani et al, [22], was reported to incorporate HA/Col with chitosan by using freezing method. The application of the composites was for cartilage tissue engineering.…”
Section: The Composites Of Ha/col/natural Polymersmentioning
confidence: 99%